Effects of Waterlogging on the Performance of Ruvu to Mlandizi Road Pavement (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
Waterlogging is a problem on the road embankment constructed from Ruvu to Mlandizi. During the rainy season, the rainwater and floods from the Ruvu River cause the water table to rise, and the water tends to infiltrate the embankment. This scenario has led to severe defects on the road pavement, such as potholes, alligator cracks, heaves and ruts, regardless of frequent maintenance conducted. This paper establishes a methodological approach aimed at assessing failures of Ruvu–Mlandizi road pavement sections. A levelling survey was conducted to establish the topographical nature of the road section. The determined levels were compared with specified requirements of road design against actual embankment heights. The results indicate that there was a need to raise the embankment to appropriate heights to accommodate flood levels and overcome water overtopping the road. The excavation of two trial pits to determine the actual depth of the water table on a road section was also conducted. Results reveal that the water table was at a depth of 0.3 m from the top of the improved subgrade surface. Based on the study findings, it is recommended to improve the road embankment heights of 1.5 m and apply appropriate methods to reinstate the situation.